The Effect of Family Empowerment on Self-Care Motivation in Hypertension Patients: Literature Review - Agus Meriroja; Rondhianto Rondhianto; Anisah Ardiana (Jurnal Ners, 2025)
Hypertension is a common health problem among the elderly, and its management requires high self-care motivation. Family empowerment has been shown to have a significant effect on increasing self-care motivation in hypertensive patients. The purpose of this study was to analyze the effect of family empowerment on self-care motivation in hypertensive patients based on the results of a literature review. Methods: The literature study was conducted using the Sciencedirect, Pubmed, and Scopus databases, with articles published between 2018 and 2024. The keywords used included "Family Empowerment", "Self-care", "Hypertension", and "Elderly". Results: Of the seven articles identified, the majority showed that family empowerment, either through direct intervention or using a digital platform, contributed to increased self-efficacy, adherence to treatment, and better blood pressure management in hypertensive patients. In addition, family support in the form of education and motivation plays an important role in creating an environment that supports self-care. Conclusion: Family empowerment plays a major role in increasing the motivation of hypertensive patients to carry out effective and sustainable self-care. Therefore, interventions involving family empowerment can be an effective strategy in managing hypertension, especially in the elderly..